Inleiding interieurontwerp. - Gibbs, Jenny, ....- (Amsterdam : Bis, 2006)
Inleiding Interieurontwerp is a practical reference book for students of interior design, but also an attractive, inspiring and educative book, a mine of information for everyone who wants to know more than what popular home interior magazines and glossy design books have to offer.
Keywords: Woninginterieurs